Nonlinear Pricing and Exclusion: I. Buyer Opportunism - Philippe Choné; Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the exclusionary properties of nonlinear price-quantity schedules in an Aghion-Bolton style model with elastic demand and product differentiation. We distinguish three regimes depending on whether and how the price of the incumbent good is linked to the quantity purchased from the rival firm. We find that the supply of rival good is distorted downwards. Moreover, given the quantity supplied from the rival, the buyer may opportunistically purchase inefficiently many units from the incumbent to pocket quantity rebates. We show that the possibility for the buyer to dispose of unconsumed units attenuates the opportunism problem and limits the exclusionary effects of nonlinear pricing.
Keywords: L12; L42; D82; D86; 330; inefficient exclusion; buyer opportunism; disposal costs; quantity rebates; incomplete information